Penentuan Sudut Kemiringan Optimum Berdasarkan Energi Keluaran Panel Surya - T. M. Azis Pandria; Muzakir Muzakir; Edi Mawardi; Samsuddin Samsuddin; Munawir Munawir; Mukhlizar Mukhlizar (Jurnal Serambi Engineering, 2021)
Angle tilt is an important factor that affects the amount of solar radiation received on the surface of solar panels. Fixed-mounted solar panels cannot receive the maximum amount of solar radiation. How to get the maximum solar radiation by positioning the surface of the solar panel at a certain slope to be directly facing the sun. This study aims at  determining  the optimum slope angle of solar panels in the city of Meulaboh (4,152 LU, 96,131 BT). The method of calculating the total value of solar radiation on a sloping surface simulated with Pvsyst Software is used to determine the annual optimum tilt angle. NASA SSE solar radiation data from 1983 – 2005 were used to support simulations in this study. The results showed that the tilt angle that can produce the maximum output energy in the city of Meulaboh (4,152 LU, 96,131 BT, Johan Pahlawan) is at an angle of 5° with the orientation directly facing south.